Desain dan Implementasi On-Board Computer/ On-Board Data Handling (OBDH) pada UGM-SAT - Bakhtiar Alldino Ardi Sumbodo; Agfianto Eko Putra (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2015)
The engineering model of OBDH for UGM-SAT was designed to control data handling program and tointerface the satellite subsystems to OBDH. The OBDH’s based on the Microchip microcontroller PIC16F877A with 20 Mhz clock speed. The system’s equipped with four external 24LC512 EEPROM’s with a storage capacity of 256 kB. The external memories’re used to store housekeeping information. The system’s equipped with a ACS712ELCTR-05B-T current sensor, voltage sensor and LM335Z temperature sensor. The accuracy of the measurements’re more than 99%. The system’s also equipped with IC Real Time Clock (RTC) DS3232M with an internal clock of 32.768 Hz, which’s used to synchronize the time between OBDH with other subsystems.The components of OBDH was chosen with industrial standards, small packages and low power. OBDH’s designed to operate in environments with extreme temperature conditions. The communication with other subsystems was designed to use I2C-bus. Protocol data for communication between the satellite subsystems have been designed. A HammingCode(8,4) algorithm has been implemented to protect housekeeping information from being corrupted due to radiation. Error detection and correction speed is 1.800 byte/s. The engineering model of OBDH for UGM-SAT have met the standard specifications, and ready for further testing hardware and software.